BLOCKCHAIN DAN CRYPTOCURRENCY REVOLUSI BARU DALAM SISTEM EKONOMI MODERN - Dodi Setiawan Riatmaja; Mira Hastin; Endah Heryanti; Khairunnisa; Sri Hastutik; Andi Zulfikar Darussalam (EDU RESEARCH, 2024)
Blockchain and cryptocurrency have emerged as global phenomena, driving significant changes in the modern economic system. Blockchain, the underlying technology of cryptocurrency, offers transparent, secure, and decentralized solutions for various applications in both financial and non-financial sectors. Cryptocurrencies, such as Bitcoin and Ethereum, have revolutionized transactions by eliminating traditional intermediaries like banks. This technology holds immense potential for fostering financial inclusion, reducing transaction costs, and improving the efficiency of payment systems. However, its implementation faces challenges, including regulation, security, and technological adoption. This paper examines the fundamental concepts of blockchain and cryptocurrency, their potential benefits in the modern economic system, and the challenges that must be addressed to optimize their use. By understanding the technical and social aspects of these technologies, stakeholders are expected to leverage blockchain and cryptocurrency to support a more equitable, efficient, and innovative global economic transformation.